"A Different Way to Survive": The Experiences of Family Caregivers of Persons Living With Dementia During the COVID-19 Pandemic. (August 2022) - Masoud, Sara; Glassner, Ashlie A.; Mendoza, Mayra; Rhodes, Shanae; White, Carole L.
Family caregivers of persons living with dementia often experience challenges to their health and quality of life related to their caregiving role. The COVID-19 pandemic added substantially to the responsibilities of family caregivers, potentially putting them at greater risk of poor health outcomes and impeded quality of life. To better understand the impact of the pandemic on the experiences of family caregivers, a multimethods study was conducted. Family caregivers of persons living with dementia were invited to complete a cross-sectional survey and a subset of survey respondents were invited to participate in focus groups for added insight. A total of 161 caregivers responded to the survey and 30 participated in the focus groups. Qualitative data from focus groups were used to elucidate deeper insight into quantitative findings from the survey. Findings reflect that the pandemic affected family caregiver health and wellness, access of care and resources, identity, and resilience.